Lactococcus lactis carrying the pValac DNA expression vector coding for IL-10 reduces inflammation in a murine model of experimental colitis - Zurita Turk, Meritxell (2014)
Background: Inflammatory bowel diseases (IBD) are intestinal disorders characterized by inflammation in the gastrointestinal tract. Interleukin-10 is one of the most important anti-inflammatory cytokines involved in the intestinal immune system and because of its role in downregulating inflammatory cascades, its potential for IBD therapy is under study. We previously presented the development of an invasive strain of Lactococcus lactis (L. lactis) producing Fibronectin Binding Protein A (FnBPA) which was capable of delivering, directly to host cells, a eukaryotic DNA expression vector coding for IL-10 of Mus musculus (pValac:il-10) and diminish inflammation in a trinitrobenzene sulfonic acid (TNBS)-induced mouse model of intestinal inflammation. As a new therapeutic strategy against IBD, the aim of this work was to evaluate the therapeutic effect of two L. lactis strains (the same invasive strain evaluated previously and the wild-type strain) carrying the therapeutic pValac:il-10 plasmid in the prevention of inflammation in a dextran sodium sulphate (DSS)-induced mouse model. Results: Results obtained showed that not only delivery of the pValac:il-10 plasmid by the invasive strain L. lactis MG1363 FnBPA+, but also by the wild-type strain L. lactis MG1363, was effective at diminishing intestinal inflammation (lower inflammation scores and higher IL-10 levels in the intestinal tissues, accompanied by decrease of IL-6) in the DSS-induced IBD mouse model. Conclusions: Administration of both L. lactis strains carrying the pValac:il-10 plasmid was effective at diminishing inflammation in this murine model of experimental colitis, showing their potential for therapeutic intervention of IBD.